Biomechanical quantification of the key parameter related to the forehand overhead smash in badminton - Shan, G.; Li, S.; Meng, M. (6th World Congress of Racket Sport Science, 2018)
One of the dominant skills in badminton is the forehand overhead smash, which consists of 1/5 attacks during games. Empirical evidences show that one has to adjust the body position in relation to the coming shuttlecock to produce a powerful and accurate smash. A search of literature has shown that there is a dearth/lack of study on this fundamental aspect. The goal of this study was to determine the influence of positioning on smash quality in order to discover information that could help coaching. Using a 10-camera, 3D motion capture system (VICON, 200 frames/s) and 15-segment, full-body biomechanical model, 10 skilled and 10 novice players were measured and analysed. Results have revealed that the body positioning has direct influence on the quality of a smash, especially on shuttlecock release angle and clearance height (passing over the net) of offensive players. The results also suggest that, for training a proper positioning, one could conduct a self-selected comfort position towards a statically hanged shuttlecock and then step one foot back - a practical reference marker for learning. This perceptional marker could be applied in guiding beginners learning. The researchers hope that the findings will benefit practitioners for developing effective training programs for beginners.